The role of zakat for poverty alleviation and income inequality reduction - Ayuniyyah, Qurroh; Pramanik, Ataul Huq; Md Saad, Norma; Ariffin, Muhammad Irwan (2017)
This research aims to analyze the role of zakat distribution program specifically in eradicating poverty and reducing income inequality among groups in urban and rural areas. The research takes the case study of 1,309 zakat beneficiaries managed by the National Zakat Board of Indonesia (abbreviated as BAZNAS) as the coordinating zakat institution in Indonesia, in five different cities and regencies in West Java Province namely, Bogor, Depok and Sukabumi. The analytical tools used in the study are the modification of the Center of Islamic Business and Economic Studies (abbreviated as CIBEST) model that assesses poverty from material and spiritual perspectives as well as CHAID analysis to see which variables are statistically significant in influencing the change in income and spiritual condition of the respondents. In addition, Deciles method and Gini coefficient are also employed to measure the effect of zakat on income inequality reduction among zakat beneficiaries under consideration. This study suggests that the present zakat distribution programs conducted by BAZNAS can significantly alleviate poverty and reduce income inequality among zakat beneficiaries. It is also found that spiritual supervision and routine assistance form BAZNAS officers, informal education, family size, age and job of the respondents are the variables that are statistically significant in influencing the increase of the households’ income and spirituality. This study is expected to exhibit how zakat can benefit the economy of a country. The study is also expected to provide some policy recommendations for the government to optimize the role of zakat in the development process.